1998
DOI: 10.1080/01652176.1998.9694958
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cattle exposed to foot‐and‐mouth disease virus by means of an indirect ELISA test using bioengineered nonstructural polyprotein 3ABC

Abstract: PROCEEDINGSdeveloped, particularly for detecting the circulation of FMD virus in a subclinical form in FMD-vaccinated populations.When adapted for use in sheep, the 3ABC MAt-ELISA showed similar specificity, giving negative results with sera from vaccinated animals and positive in experimentally infected sheep that developed antibodies to FMDV structural proteins. In field conditions, the test was able to detect silent infections in asymptomatic sheep. However, there was more variation in antibody levels in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
20
1
Order By: Relevance
“…No previous publications mention this kit, although several studies used a similar format with an E. coli-expressed protein. The parameter estimates were high, with an Se of 100% and an Sp of 99% in cattle 20 days postinfection (31) and an Se of 92% and an Sp of 90% in sheep (7). However, these studies were based on small, experimentally infected groups rather than naturally infected populations.…”
Section: Discussionmentioning
confidence: 99%
“…No previous publications mention this kit, although several studies used a similar format with an E. coli-expressed protein. The parameter estimates were high, with an Se of 100% and an Sp of 99% in cattle 20 days postinfection (31) and an Se of 92% and an Sp of 90% in sheep (7). However, these studies were based on small, experimentally infected groups rather than naturally infected populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant c3B was generated using a synthetic codon-optimized gene in BL21 E. coli. Previous studies that used E. coliexpressed proteins to develop FMDV diagnostic tests required the addition of E. coli lysates to sample serum diluents, to preabsorb nonspecific background reactivity (39,52). It has been suggested that this background reactivity may be due in part to inclusion of the N-terminal 3A sequence, which shares sequence homology with a transposase IS4 family protein from E. coli (53).…”
Section: Discussionmentioning
confidence: 99%
“…The reference DIVA test adopted by the OIE for FMDV is an ELISA that detects antibodies against the NSP 3ABC (NCPanaftosa screening test) complemented by an enzyme-linked immunoelectrotransfer blot assay (12,38). A problem associated with the use of 3ABC is the presence of vaccine-associated 3A protein, which may complicate DIVA testing due to the presence of 3A-specific antibodies in sera from some vaccinated cattle (15,39,40). Furthermore, due to its expression as insoluble inclusion bodies in E. coli and the presence of the autocatalytic 3C protein segment, recombinant 3ABC is difficult to produce (28, 41-43; our unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the antibody response against NSPs is variable; 3A, 3B, 3D and 3 ABC could be detected in cattle as early as 7-10 days post infection (Bergmann et al, 1993;Sorensen et al, 1998) and up to 560-742 days post infection (Silberstein et al, 1997;Malirat et al, 1998). However, in sheep, these develop later; against 3ABC at 14 days and against 3D after 22 days post infection.…”
Section: Differentiation Of Infected and Vaccinated Animals (Diva)mentioning
confidence: 99%